The study of youth awareness on government program in combating corruption / Mohd Shazwan Mohd Yusof and Nissy Felicia Banati - Mohd Yusof, Mohd Shazwan; Banati, Nissy Felicia (2014)
This research tends to measure the level of youth awareness on government program in combating corruption. To obtain the result for this study, we using primary data which is by distributing a questionnaire to the respondents. Around 100 respondents were given questionnaire in order to obtain the result which later will be analyzing using SPSS. The distribution of data were only around Sepanggar area because the youth around this area mostly youth. Based on the findings we get, the result shown that the level of youth awareness on government program was in moderate level. Hence, the government still has to do their best in combating corruption by giving the youth to take part in combating corruption.